Dynamics of Human–Water Interactions in the Kilombero Valley, Tanzania: Insights from Farmers' Aspirations and Decisions in an Uncertain Environment - Britta Höllermann; Kristian Näschen; Naswiru Tibanyendela; Julius Kwesiga; Mariele Evers (The European Journal of Development Research, 2021)
The Kilombero Valley, one of East Africa's largest seasonal wetlands, is a high-potential agricultural development corridor area in Tanzania. This seasonally flooded wetland is mainly used by smallholder farmers who cultivate during the rainy season, although there are some community-based irrigation systems that reduce hydro-climatic risks. In this study, we aim to understand how farmers' aspirations and visions about the future are related to the current agricultural practices and human–water interaction. We specifically investigate the differences between farmers from rainfed and irrigated agriculture by using focus group discussions. Analysis of the in-depth interviews highlights how farmers' actions both shape and respond to this highly dynamic and uncertain environment. Furthermore, we identify a close link, driven by the farmers' level of agency, between aspirations and expected agro-economic development. The heterogeneity of farmers' agency and hence their ability to cope with change is not only based on the socioeconomic status but also on their perception of the physical environment. We thus recommend that attention is also paid to the capacity for coping with environmental challenges that influences the level of farmers' aspiration.
Keywords: 330; Hydro-climatic risk; Smallholder farmers; Decision-making under uncertainty; Focus group discussions; Aspiration gap; Agro-economic development